A Note on ‘Yagur of the Talmud’ - Press, Michael D. (Liber Annuus, 2012)
Abstract Standard gazetteers and geographies of Roman and Byzantine Palestine typically include a short reference to a Roman and Byzantine village named Yagur, located on the outskirts of Ashkelon and identified with the Arab village of El Jura. The references to this purported village cite as evidence a passage in the Tosefta (tAhil. 18:15). However, Yagur is nowhere mentioned in the Tosefta; it first occurs in an emended quotation of this passage by the medieval French rabbi Rash, in his Mishnah commentary. This article demonstrates that there is no evidence to support the Rash’s emendations as the original readings of the passage, and therefore removes all evidence for the existence of a Roman/ Byzantine Yagur.